2018
DOI: 10.2134/jeq2017.07.0280
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, Intermediate Soil Carbon Pools May Drive Future Responsiveness to Environmental Change

Abstract: Accurately capturing dynamic soil response to disturbance effects in agroecosystem models remains elusive, thereby limiting projections of climate change mitigation potential. Perennial grasses cultivated in zero-tillage management systems hold promise as sustainable agroecosystems. High-yielding tropical C grasses often have extensive rooting systems, and the belowground processes of root turnover, aggregate formation, and mineral stabilization drove rapid C accumulation after cultivation in a recent study. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The emphasis on improving crop and climate inputs to soil C cycling model components should not imply that our fundamental understanding of the soil processes regulating the transformation of plant residues and models depicting those processes are not also in need of improvement. As shown by both Crow and Sierra (2018) and Sherrod et al (2018), there is a need for better understanding and model representation of the responses of different pools of soil C to climate and management, as well as transfers of C among those pools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis on improving crop and climate inputs to soil C cycling model components should not imply that our fundamental understanding of the soil processes regulating the transformation of plant residues and models depicting those processes are not also in need of improvement. As shown by both Crow and Sierra (2018) and Sherrod et al (2018), there is a need for better understanding and model representation of the responses of different pools of soil C to climate and management, as well as transfers of C among those pools.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen contributions to this special section applied dynamic process-based models to assess the effects of climate and/or management on SOC dynamics. As described below, seven papers used the CQESTR model, whereas other models included were DeNitrification-DeComposition (DNDC), DayCent, CENTURY, RothC, the Model for Nitrogen and Carbon in Agro-Ecosystems (MONICA), the Environmental Productivity Integrated Climate (EPIC) model, and a detailed mathematical model of soil C dynamics devised by Crow and Sierra (2018). Cavigelli et al (2018) used SOC data from the long-term Farming Systems Project and the CQESTR model to examine the impact of projected climate change on SOC to 50-cm soil depth for grain cropping systems in the Mid-Atlantic United States.…”
Section: Process-based Models To Evaluate Soil Organic Carbon Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mismatch has led to the conclusion that C-cycling in soils may not be thermodynamically limited, but rather that it is kinetically limited. Furthermore, kinetic limitations of C-turnover are linked to carbon sorption on particles [e.g., Crow and Sierra (2018)] and processes of aggregation (Kalinina et al, 2015;Crow and Sierra, 2018). However, because the effective temperature and the aggregate turnover are controlled by BSM, and that in the longtime limit Cmobility is essentially diffusive, this implies that carbon turnover rate is proportional to the effective temperature (Equation 13) through the temperature dependency of diffusion itself (Loi et al, 2011a).…”
Section: Integrating Aggregate Turnover Within Carbon Cycling Modelsmentioning
confidence: 99%
“…For example, aggregate formation and stability were affected by soil type in giant miscanthus in the midwestern United States, thereby reducing the protection of recent C inputs from losses in some cases (Tiemann & Grandy, 2015). In contrast, the dynamic transfer of fresh inputs from roots through aggregates and into organo‐mineral stabilized pools drove the rapid soil C accumulation measured in tropical perennial C 4 grasses (Crow, Deem, Sierra, & Wells, 2018; Crow & Sierra, 2018). In another study, Plaza, Courtier‐Murias, Fernández, Polo, and Simpson (2013) similarly found that organo‐mineral interactions increased soil C by 16% under no‐till compared to conventional management.…”
Section: Introductionmentioning
confidence: 99%